Methicillin-resistant Staphylococcus aureus on hospital admission in Turkey - (:unkn) unknown (MOSBY-ELSEVIER, 2009)
A total of 400 patients were screened for methicillin-resistant Staphylococcus aureus (MRSA) on hospital admission, and 11 MRSA strains (1.2%) were detected. All 11 MRSA strains were positive for the mecA and PVL genes. Eight of the 11 MRSA-positive patients (72%) had a history of hospitalization within the previous 12 months. Copyright (c) 2009 by the Association for Professionals in Infection Control and Epidemiology, Inc.
Keywords: RISK-FACTORS; CARRIAGE; PREVALENCE; RATES; MRSA